2017
DOI: 10.1016/j.jagp.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Delirium's Heterogeneity: Association Between Arousal Subtypes at Initial Presentation and 6-Month Mortality in Older Emergency Department Patients

Abstract: Objectives To determine how delirium subtyped by level of arousal at initial presentation affects 6-month mortality. Design This was a preplanned secondary analysis of two prospective cohort studies. Setting Academic tertiary care emergency department (ED). Participants 1,084 ED patients who were 65 years old or older. Measurements At the time of enrollment, trained research personnel performed the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) and Richmond Agitation Sedation Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…However, it is still unclear how level of arousal relates to prognosis in patients with delirium. Han et al (2017) observed in a cohort of 1,084 older adults from the emergency department that only delirium with normal arousal was significantly associated with increased mortality, compared to the no delirium group [ 37 ]. Further studies are needed to understand the clinical value of subtyping delirium only according to arousal level as compared to assessing additional characteristics of psychomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear how level of arousal relates to prognosis in patients with delirium. Han et al (2017) observed in a cohort of 1,084 older adults from the emergency department that only delirium with normal arousal was significantly associated with increased mortality, compared to the no delirium group [ 37 ]. Further studies are needed to understand the clinical value of subtyping delirium only according to arousal level as compared to assessing additional characteristics of psychomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Level of arousal can be decreased, increased, or normal. In 1,084 older ED patients, delirium with normal arousal was the only arousal subtype associated with sixmonth mortality (Han et al, 2017a). Delirium can vary by severity.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is a heterogeneous syndrome in terms of its phenomenology, duration, severity, and presence of predisposing factors. Several studies suggest that variations in psychomotor activity, (Kiely et al, 2007;Meagher et al, 2011;Kim et al, 2015;Jackson et al, 2016) level of arousal, (Han et al, 2017a) severity, (Kelly et al, 2001;Inouye et al, 2014;Jackson et al, 2016;Vasunilashorn et al, 2016aVasunilashorn et al, , 2016b duration of delirium, prior cognitive impairment, and other comorbidities differentially affect outcomes of delirium (Jackson et al, 2016;Davis et al, 2017;Han et al, 2017a). There is also some limited evidence that physiological variables, such as increased inflammatory biomarkers, may influence outcomes, (Vasunilashorn et al, 2017) suggesting the possibility that particular triggers of delirium such as those inducing inflammatory states may have more impact on outcomes than other etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Inattention is determined based on the number of errors that occur when having the patient squeeze the examiner's fell to a RASS score of ≤ −2, more than half of participants had inaccurate assessment findings or were not able to be assessed. Of particular concern in older (≥50 years) adults, accuracy is significantly lower (31-64%) in patients experiencing the hypoactive subtype (Han et al, 2017;van Velthuijsen, Zwakhalen, Mulder, Verhey, & Kempen, 2017).…”
Section: Setting/samplementioning
confidence: 99%